Decomposing Change in Energy Consumption of the Agricultural Sector in Pakistan. (December 2014) - Ahmed, Vaqar; Zeshan, Muhammad
The agricultural sector provides the majority of employment in Pakistan, especially among the poorest segments of the population. Energy provision affects production and livelihoods, especially with the advance of mechanization in agriculture. Changes in gas and electricity prices affect the income of farmers significantly, thereby reducing the agricultural growth rate over time. Agriculture also has a positive impact on industrial sector exports. The dependence of agriculture on electricity consumption in Pakistan has increased over time, while power generation has not kept up with demand. This article decomposes energy consumption in Pakistan and analyzes the behaviour of change in agricultural production, energy intensity and structural changes over the time.